2019
DOI: 10.1177/1938640019895917
|View full text |Cite
|
Sign up to set email alerts
|

Structures at Risk During Percutaneous Extra-Articular Chevron Osteotomy of the Distal First Metatarsal

Abstract: Background. Minimally invasive surgery of the forefoot has regained popularity as an alternative to traditional open procedures. Minimally invasive hallux valgus surgery has been shown to be effective and reproducible for the treatment of mild to moderate hallux valgus. The aim of this study is to identify vital structures that are at risk for iatrogenic damage while performing a minimally invasive distal chevron osteotomy due to limited direct visualization. Methods. Ten fresh-frozen below knee cadavers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…This wound complication rate of 2% is lower than those seen in many open bunion procedures; reported rates for open procedures vary based on the type of osteotomy performed, with pooled rates of 1.5% in metatarsal shaft osteotomies, 2.5% in distal metatarsal osteotomies, and 11% in Lapidus procedures. 1,15,21 Because the third-generation MICA technique uses 2 percutaneous screws for more stable fixation compared to prior MIS techniques, we agree that larger corrections are possible than typically associated with the chevron/Akin technique. 14,20 We do feel that a large part of the stability of the MICA osteotomy and high union rate is due to the minimal soft tissue disruption associated with the percutaneous procedure and the bicortical nature of the proximal metatarsal screw, as initially described by Redfern et al 25 The chevron/Akin osteotomy has classically been indicated for IMA angles of less than 14 degrees, due to the concern that with correction of a larger deformity, there would not be enough bony contact between the head and shaft.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This wound complication rate of 2% is lower than those seen in many open bunion procedures; reported rates for open procedures vary based on the type of osteotomy performed, with pooled rates of 1.5% in metatarsal shaft osteotomies, 2.5% in distal metatarsal osteotomies, and 11% in Lapidus procedures. 1,15,21 Because the third-generation MICA technique uses 2 percutaneous screws for more stable fixation compared to prior MIS techniques, we agree that larger corrections are possible than typically associated with the chevron/Akin technique. 14,20 We do feel that a large part of the stability of the MICA osteotomy and high union rate is due to the minimal soft tissue disruption associated with the percutaneous procedure and the bicortical nature of the proximal metatarsal screw, as initially described by Redfern et al 25 The chevron/Akin osteotomy has classically been indicated for IMA angles of less than 14 degrees, due to the concern that with correction of a larger deformity, there would not be enough bony contact between the head and shaft.…”
Section: Discussionmentioning
confidence: 52%
“…However, it does not appear that the medial prominence was shaved down with the side-cutting burr in these cadaveric specimens, as is typically done after translating the osteotomy; it is thought that the dorsomedial cutaneous nerve is theoretically most at risk during that step of the procedure. Indeed, a similar cadaveric study done by McGann et al, 21 in which a medial eminence resection was also done, showed damage to the dorsomedial cutaneous nerve in 5 of 10 cadaveric specimens. It is important to note that, for the medial eminence resection, they did shave with an outside-in technique, as opposed to the inside-out technique that we use and previously described by Redfern et al 25 Techniques we use to limit the risk of nerve damage include using an inside-out technique, in which a wafer of prominent bone is cut and then removed, as opposed to an outside-in technique, in which the prominent bone is burred down from medial to lateral.…”
Section: Discussionmentioning
confidence: 72%
“…There was no apparent damage to the arterial plexus supplying the first metatarsal head and no flexor or extensor tendon injuries were identified [7]. However, McGann et al [8] reported a different outcome from the previous study. They proposed that minimally invasive chevron distal osteotomy and medial eminence resection has a high learning curve.…”
Section: Discussionmentioning
confidence: 84%
“…Following metatarsal osteotomy, some surgeons opt to perform medial eminence resection in order to achieve a more esthetically pleasing outcome. A cadaveric study revealed that in half of the specimens, the DMCN was compromised after undergoing the minimally invasive distal chevron osteotomy and medial eminence resection [ 7 ]. However, a separate study found that none of the DMCNs were injured in cases where the MICA was performed without medial eminence resection [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 3rd and 4th generation MIS is capable of achieving radiologic and clinical outcomes that are equal to, if not better than, open surgery [ 3 6 ]. However, there is a risk of damaging anatomical structures, such as the dorsomedial cutaneous nerves (DMCN), during MIS without an open incision [ 7 , 8 ]. Several studies have discussed the course of DMCN and methods to prevent nerve injuries at the metatarsophalangeal joint level (MTPJ) during metatarsal osteotomy [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%